2004
DOI: 10.1029/2004jd004978
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the photochemical environment of the temperate North Pacific troposphere in response to increased Asian emissions

Abstract: [1] Measurements during the Intercontinental Transport and Chemical Transformation 2002 (ITCT 2K2) field study characterized the springtime, eastern Pacific ozone distribution at two ground sites, from the National Oceanic and Atmospheric Administration WP-3D aircraft, and from a light aircraft operated by the University of Washington. D. Jaffe and colleagues compared the 2002 ozone distribution with measurements made in the region over the two previous decades and show that average ozone levels over the easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 43 publications
(78 reference statements)
7
113
0
Order By: Relevance
“…The focus of this paper is on all of west coast, North American MBL data that have been collected with the Oltmans et al (2006Oltmans et al ( , 2008 that the previously derived trends do not represent the marine troposphere. We find results here that are fully consistent with the conclusions presented by Jaffe et al (2003) and Parrish et al (2004a), with the statistical confidence considerably improved. It is shown that the data sets on which Oltmans et al (2006Oltmans et al ( , 2008 based their suggestions have serious shortcomings.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…The focus of this paper is on all of west coast, North American MBL data that have been collected with the Oltmans et al (2006Oltmans et al ( , 2008 that the previously derived trends do not represent the marine troposphere. We find results here that are fully consistent with the conclusions presented by Jaffe et al (2003) and Parrish et al (2004a), with the statistical confidence considerably improved. It is shown that the data sets on which Oltmans et al (2006Oltmans et al ( , 2008 based their suggestions have serious shortcomings.…”
Section: Introductionsupporting
confidence: 81%
“…Investigators have presented evidence that the background O 3 has increased since the mid-1980s at northern mid latitudes in air entering both the North American west coast form the North Pacific Ocean (Jaffe et al, 2003;Parrish et al, 2004a) and the European west coast from the North Atlantic Ocean (Simmonds et al, 2004;Derwent et al, 2007). Parrish et al (2004a) argue that the increase in the North Pacific has occurred in response to increasing Asian emissions of O 3 precursors, which are transported to the North Pacific troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are multiple lines of evidence that springtime O 3 concentrations are increasing over western North America Chan and Vet, 2010;Parrish et al, 2009;Jaffe et al, 2003;Jaffe and Ray, 2007;NRC, 2010;Parrish et al, 2004). The most recent analysis by Cooper et al (2010) showed a strong increase in lower free tropospheric (FT) springtime O 3 mixing ratios from 1995 to 2008.…”
Section: The Impact Of Asian Emissions Of Omentioning
confidence: 99%